MMP-9-mediated regulation of hypoxia-reperfusion injury-related neutrophil inflammation in an in vitro proximal tubular cell model. Issue 1 (1st January 2021) - Dong, Yan; Zhao, Hong; Man, Jiangwei; Fu, Shengjun; Yang, Li
Abstract: Background: Hypoxia-reperfusion (HR) and inflammation are causes of renal allograft injury. Pathological evidence has indicated that ischemia followed by reperfusion leads to the proteolysis and destruction of the extracellular matrix (ECM) in renal tubular epithelial cells. Matrix metalloproteinases (MMPs), such as MMP-2 and MMP-9, play roles in cleaving and reshaping the ECM. Acute accumulation of MMP-9 secreted from neutrophils promotes the incidence of inflammation and exacerbates graft trauma. Our goal was to investigate the activities of MMP-9/MMP-2 and their correlation with HR injury and neutrophil-related inflammation in renal proximal tubular cells. Methods: This model was established by placing HK-2 cells under hypoxic conditions (5% CO2, 1% O2 ) for 6 h and then exposing them to reperfusion (5% CO2, 21% O2 ) for 12 h in a tri-gas incubator. The cell culture medium was collected for culturing polymorphonuclear leukocytes (PMNs). BB-94 (MMP-9 inhibitor) was added to the culture medium in the inhibitor group. Results: Flow cytometry showed a significant increase in reactive oxygen species (ROS) levels in HK-2 cells from the HR injury group. MMP-9 expression was significantly increased and MMP-2 expression was significantly decreased in HK-2 cells from the HR group. MMP-9 and MPO expression were significantly increased in the HR group, while MPO expression was significantly decreased in the PMN inhibitor group. Conclusions: The outcomes indicated that MMP-9 and MMP-2 are important components of an underlying pathophysiological mechanism of injury following HR. MMP-9 inhibition may be a potential approach to mitigateHR injury.